1991
DOI: 10.2116/analsci.7.485
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Membrane Thallium(I)-Selective Electrodes Based on Dibenzo-crown-6 Ethers

Abstract: Keywords Thallium(I)-selective electrode, polymer membrane, ring-enlarged dibenzo-crown-6 ether From an environmental viewpoint, estimations of thallium-ion concentration have become of major interest due to their high toxicity. Ion-selective electrodes are one of the most convenient and reliable analytical tools for estimating metal-ion concentrations. There have been only a few reports concerning liquid-membrane thallium(I)-selective electrodes (Tl+-ISEs).'_4 They need to be improved with regard to both thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…From these values it can be seen that the sensor is characterized by a high selectivity towards thallium ions with respect to alkali metal ions (Li + , Na + , K + , Rb + and Cs + ), alkaline earth metal ions (Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ ), transition metal ions (Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ , Cd 2+ and Hg 2+ ) and other cations (Ag + , NH 4 + , Pb 2+ , UO 2 2+ , Cr 3+ , Al 3+ and La 3+ ). The proposed thallium sensor exhibits good response and selectivity compared with previously described sensors [5][6][7][8][9][10][11] (see Table 4). It exhibits much better slope (59 mV per decade), linearity (0.1-1.0 × 10 −6 mol l −1 ) and potentiometric selectivity for Tl + over many cations for the proposed sensor compared to other sensors.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…From these values it can be seen that the sensor is characterized by a high selectivity towards thallium ions with respect to alkali metal ions (Li + , Na + , K + , Rb + and Cs + ), alkaline earth metal ions (Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ ), transition metal ions (Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ , Cd 2+ and Hg 2+ ) and other cations (Ag + , NH 4 + , Pb 2+ , UO 2 2+ , Cr 3+ , Al 3+ and La 3+ ). The proposed thallium sensor exhibits good response and selectivity compared with previously described sensors [5][6][7][8][9][10][11] (see Table 4). It exhibits much better slope (59 mV per decade), linearity (0.1-1.0 × 10 −6 mol l −1 ) and potentiometric selectivity for Tl + over many cations for the proposed sensor compared to other sensors.…”
Section: Resultsmentioning
confidence: 77%
“…Poly(vinyl chloride) (PVC) membrane Tl + ion selective electrodes based on bis(crown ether)s containing the benzo-15-crown-5 moiety were described [7]. These crown ether based ISEs showed that the T1 + selectivity against K + for one of the bis(15-crown-5)s (Bis-15) was fairly poor (log K dibenzo-18-crown-6 (DB-18), dibenzo-20-crown-6 (DB-20) and dibenzo-22-crown-6 (DB-22) based T1 + ion selective PVC membrane electrodes were reported [8]. These sensors showed a linear response to the T1 + activity over a range of 3.2 × 10 −5 to 1.0 × 10 −2 mol l −1 TlNO 3 , with a slope of 59 mV per decade.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, the proposed electrode in terms of selectivity coefficient is superior to all of the thallium ionselective electrodes reported in the literature. [7][8][9][10] The proposed thallium ion-selective electrode was found to work well under laboratory conditions. This electrode was used as an indicator electrode in the titration of thallium(I) with K 2 S, and the resulting titration curve is shown in Figure 6.…”
Section: Khdfwxdosrwhqwldoyhuvxvwlphwudfhlvvkrzqlq)ljxuh $Vfdqehvhhqmentioning
confidence: 99%
“…Crown ether and calix [4]aren derivatives have been tested as thallium(I)-neutral carriers for ion-selective electrodes, [3][4][5][6][7][8][9][10][11][12] and the resulting thallium(I)-selective electrodes gave good results. However, since crown ethers and calix [4]arens generally have a high affinity for alkali-metal ions and in some cases silver, these thallium(I) electrodes suffer from severe interference by Na In the present study, we wish to introduce a novel thallium(I) electrode by incorporation of a podal ligand as a suitable neutral ionophore for fast monitoring of thallium ion.…”
Section: Introductionmentioning
confidence: 99%
“…ISMEs have been used to measure the fluxes of Cd 2+ , K + , Ca 2+ , H + , and NH 4 + into the roots of wheat, maize, and barley (Piñeros et al 1998;Ryan et al 1990;Newman 2001). Although different Tl + ISEs have been described (Park et al 2000;Yamashoji et al 1991;Khayatian et al 2003;Kimura et al 1999;Ganjali et al 2003), there is no literature on Tl + ISMEs, which could have a great application for measuring spatial Tl + flux to examine K + competition at specific sites along a root.…”
Section: Introductionmentioning
confidence: 99%